Shift in the Funding Theory Paradigm: From Newtonian-Positivistic to Critical-Phenomenology - Maria Rio Rita; Sony Heru Priyanto (Jurnal Keuangan dan Perbankan, 2017)
Theories about funding have developed rapidly, it was starting from the traditional-rational theory to the behavior-based funding theory, which response to the gap between reality and financial theories. The theoretical developments can depict the real condition of financial management involving funding decisions, investment decisions, and dividend policies in an enterprise. These developments and evolution enable financial managers and also entrepreneurs to realistically apply them in their business activities. This research used a meta-synthesis analysis technique to integrate results from a number of different but inter-related qualitative studies. There has already been a shift in the funding theory paradigm from a Newtonian paradigm which emphasizes positivistic epistemology leading to a Critical paradigm, which places more emphasis on a phenomenological approach to see the reality. This shift has resulted in many changes related to the financial essence, research related to financing, as well as the advantages of the funding or financing theory in a company. A new essence about funding has surfaced, where funding and its benefits can solve company funding problems. DOI: https://doi.org/10.26905/jkdp.v21i4.1510